Nodes deployment strategy for underwater wireless sensors networks based on grids - Kai ZHOU (Dianxin kexue, 2018)
To optimal the node deployment of underwater wireless sensor network,a node deployment strategy with multi-metrics based on the grids was proposed.Firstly,the underwater environment was divided into some certain size grids.Then,based on number of nodes,coverage quality of nodes,lifetime of network,network redundancy,a multi-objectives model was proposed.In order to solve the model,cost function with constraint conditions was given.Based on the genetic algorithm,the cost and the energy consumption of the deployment method were computed.The simulation result shows that the energy consumption and the number of deployment nodes are reduced.